If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(3x + -11) = 1 + 7x Reorder the terms: 11x + -1(-11 + 3x) = 1 + 7x 11x + (-11 * -1 + 3x * -1) = 1 + 7x 11x + (11 + -3x) = 1 + 7x Reorder the terms: 11 + 11x + -3x = 1 + 7x Combine like terms: 11x + -3x = 8x 11 + 8x = 1 + 7x Solving 11 + 8x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 11 + 8x + -7x = 1 + 7x + -7x Combine like terms: 8x + -7x = 1x 11 + 1x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 11 + 1x = 1 + 0 11 + 1x = 1 Add '-11' to each side of the equation. 11 + -11 + 1x = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 1 + -11 1x = 1 + -11 Combine like terms: 1 + -11 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| -2/5x=2/5 | | 75=3/5x | | 6x=3x+18x | | 9+4=4r-3-6 | | x=-2x+20 | | y=-(0.67x+1.67) | | 2a+7b+2a+5b= | | 4r+8=8+4 | | x^2+500x=0 | | 9=1-2b/5 | | 10/13=50/65 | | 17x-19y=61 | | X^2y=125 | | -8x+8y=12 | | 2r+8=12 | | -3x/4-8=4 | | n^4-(s-x)n^2+2x(35-x)=0 | | n^4-(s-x)n^2+2x(3s-x)= | | R/3-2=-7 | | f(x)=0.75x+0.25 | | n^4-(s-x)n^2+2x(35-x)= | | x^2+1=132 | | x^2+1=131 | | 8x-0.25= | | x^2=131 | | x*2=131 | | 5+2k=-3 | | 1+3p=10 | | 8=6+2c | | 6/7-2i | | 0.75p=0.4+100 | | Y=13.50X-350 |